Focus group interview as a means to determine school effectiveness indicators / Sueb Ibrahim ... [et al.] - Ibrahim, Sueb; Aperapar Singh, Parmjit Singh; Choo, Ng Kui; Boje, Ramilah (Universiti Teknologi MARA Cawangan Sarawak, 2018)
The growth of interest in school effectiveness has been striking and is gaining momentum. Similarly in Malaysia, school effectiveness has become a dominant theme in contemporary educational reform and development. Thus, the growing concern about educational reform has resulted in a wide variety of school effectiveness interventions, initiatives and strategies. Although school effectiveness has become the central focus in most schools, there is still a strong need to determine the constructs or dimensions that are suitable to measure school effectiveness in Malaysian secondary schools. In this study, a focus group interview consisting of eight selected excellent and senior school principals were conducted. The findings from the focus group interview indicated 5 indicators for school effectiveness which comprised academic performance, school programme, organizational effectiveness, learning environment and school achievement. The findings also indicated 15sub-indicators for school effectiveness consisting of curriculum, public exam, student assessment, academic programme, co-curriculum programme, student development, resource management, technology advancement, data and information management, teaching and learning, community relation, staff professional development,, award and recognition, innovation and niche area